Analysıs of Urınary Albumın and Urınary Synaptopodın Levels in Type 2 Dıabetes Mellıtus Subjects - Afni Juhairia Laisouw; Liong Boy Kurniawan; Yuyun Widaningsih; Tenri Esa; Himawan Sanusi; Andi Alfian Zainuddin; Theosobia Grace Orno (Medical Laboratory Technology Journal, 2023)
Hyperglycemia from diabetes mellitus affects many body organs and interferes with normal function. Kidney function decreased in approximately one-third of patients with diabetes mellitus before the development of albuminuria. The purpose of this study was to analyze differences in urine albumin and urine synaptopodin levels in type 2 diabetes mellitus (T2DM) and non-DM subjects, differences in urine synaptopodin levels in T2DM subjects with and without nephropathy, to analyze the correlation between urine albumin and urine synaptopodin in T2DM subjects and the cut-off analysis of sensitivity and specificity of urinary synaptopodin in diagnosing diabetic nephropathy. A sample of 60 subjects comprised 40 T2DM subjects and 20 non-DM subjects. Urinary synaptopodin levels were examined using the ELISA method, and albuminuria levels using the immunoturbidimetric method. Based on statistical analysis, the results showed that there were differences in urine albumin levels in T2DM and non-DM subjects (p*= < 0.001), there were differences in urine synaptopodin levels in T2DM and non-DM subjects (p*= < 0.001), there were no differences in urine synaptopodin levels with and without nephropathy in T2DM subjects (p*= 0.090), a relationship was found between urine albumin and urinary synaptopodin in T2DM subjects (p*= 0.048, r= 0.314) and the cut off of urinary synaptopodin in diagnosing nephropathy was ³0.39 ng/mL, sensitivity 64.7% and specificity 56.5%. We recommend further prospective studies with larger sample sizes to compare urinary synaptopodin levels and microalbuminuria (MAU) as markers for early detection of DN in T2DM subjects.